Cell-marking techniques for cell lineage tracing - A. M. Yunusova; N. R. Battulin (Вавиловский журнал генетики и селекции)
A zygote, the only totipotent cell of the developing organism, transforms into a complex, multicellular entity with billions (for humans) of highly specialized cells and tissues. Most adult tissues are maintained by a combination of highly dynamic processes of senescence, apoptosis and rejuvenation with new cells constantly arising from dispersed depots of stem cells. Studying individual cell fates and their intertwined relations thus aids in understanding ontogenetic development as well as pathogenic processes in the body. Direct observations of developing embryos uncovered the fate of single blastomeres of ascidia and nematode. In both cases, research benefited from the simplicity of these objects, because, in ascidia, each blastomere has unique signatures naturally, and, in nematode, transparency of a worm’s 959-cell body allows every cell to be traced through development individually. In most cases, however, studying cellular lineages and identification of stem cells’ subpopulations are a true challenge for investigators. To trace the cell’s fate, novel methods were invented that introduce special tags into cells, the tags that would be inherited during cell divisions. Every descendent of a marked cell bears the same tag and can easily be distinguished from unrelated cellular neighbors. This review focuses on modern methods for cell tracing with dyes and genetic constructs encoding protein reporters that mark cell lineages. Special focus is on genome-integrated tags (genetic labeling), such as viral and cellular barcoding. One chapter of the review describes novel advancements in the field of CRISPR/Cas9-based cellular barcoding.